Living in a Dangerous Climate: Climate Change and Human Evolution - Law, Matt (Ethnobiology Letters, 2014)
Review of Living in a Dangerous Climate: Climate Change and Human Evolution. Renee Hetherington. 2012. Cambridge University Press, Cambridge. Pp. 256. ISBN 978‐1107694736.